Consumer reactions in the polygraph before a propaganda about the environment - María Orquídea Escobar (GEON Journal (Management, Organizations and Business), 2015)
In marketing, it is difficult to know the reactions of consumers to advertising stimuli. These reactions often cannot be observed directly, so there is a tendency to employ specialized technology to measure the behavior of individuals to different stimuli. This research seeks to understand the psychophysiological reactions on environmental advertising in through the polygraph, on 20 people, male and female university students and professionals, aged 18 and 48, in Bogota. The results show a difference in the thoracic and abdominal breathing and evident contradictions between verbal report on the impact of advertising and reactions on the polygraph.
Keywords: Polygraph; Marketing; Consumer behavior; Advertising; Neuromarketing